Prompt Graft Cooling Enhances Cardioprotection during Heart Transplantation Procedures through the Regulation of Mitophagy - Zhichao Wu; Jialiang Liang; Wei Huang; Lin Jiang; Christian Paul; Bonnie Lin; Junmeng Zheng; Yigang Wang (Cells, 2021)
A complete and prompt cardiac arrest using a cold cardioplegic solution is routinely used in heart transplantation to protect the graft function. However, warm ischemic time is still inevitable during the procedure to isolate donor hearts in the clinical setting. Our knowledge of the mechanism changes prevented by cold storage, and how warm ischemia damages donor hearts, is extremely poor. The potential consequences of this inevitable warm ischemic time to grafts, and the underlying potential protective mechanism of prompt graft cooling, have been studied in order to explore an advanced graft protection strategy. To this end, a surgical procedure, including 10–15 min warm ischemic time during procurement, was performed in mouse models to mimic the clinical situation (Group I), and compared to a group of mice that had the procurement performed with prompt cooling procedures (Group II). The myocardial morphologic changes (including ultrastructure) were then assessed by electron and optical microscopy after 6 h of cold preservation. Furthermore, syngeneic heart transplantation was performed after 6 h of cold preservation to measure the graft heart function. An electron microscopy showed extensive damage, including hypercontracted myofibers with contraction bands, and damaged mitochondria that released mitochondrial contents in Group I mice, while similar patterns of damage were not observed in the mice from Group II. The results from both the electron microscopy and immunoblotting verified that cardiac mitophagy (protective mitochondrial autophagy) was present in the mice from Group II, but was absent in the mice from Group I. Moreover, the mice from Group II demonstrated faster rebeating times and higher beating scores, as compared to the mice from Group I. The pressure catheter system results indicated that the graft heart function was significantly more improved in the mice from Group II than in those from Group I, as demonstrated by the left ventricle systolic pressure (31.96 ± 6.54 vs. 26.12 ± 8.87 mmHg), the +dp/dt (815.6 ± 215.4 vs. 693.9 ± 153.8 mmHg/s), and the -dp/dt: (492.4 ± 92.98 vs. 418.5 ± 118.9 mmHg/s). In conclusion, the warm ischemic time during the procedure impaired the graft function and destroyed the activation of mitophagy. Thus, appropriate mitophagy activation has emerged as a promising therapeutic target that may be essential for graft protection and functional improvement during heart transplantation.